2018
DOI: 10.1038/s41598-018-35037-8
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of regulatory T cells in ongoing paracoccidioidomycosis rescues protective Th1/Th17 immunity and prevents fatal disease outcome

Abstract: In human paracoccidioidomycosis (PCM), a primary fungal infection typically diagnosed when the disease is already established, regulatory T cells (Treg) cells are associated with disease severity. Experimental studies in pulmonary PCM confirmed the detrimental role of these cells, but in most studies, Tregs were depleted prior to or early during infection. These facts led us to study the effects of Treg cell depletion using a model of ongoing PCM. Therefore, Treg cell depletion was achieved by treatment of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 63 publications
(83 reference statements)
3
21
0
3
Order By: Relevance
“…Thus, it is unexpected that mucosal Trm producing IL-17 in IN vaccinated mice were non-protective. It is possible that regulatory Trm cells, which are typically not associated with host resistance to fungal infection, dampen the protective effects of Th17 cells (de Araujo et al, 2017;Galdino et al, 2018). It has been shown, that zymosan (predominantly composed of β1,3 glucan) can induce anti-inflammatory effects on T cell differentiation and promote the generation of regulatory T cells (Caminschi et al, 2019;Dillon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unexpected that mucosal Trm producing IL-17 in IN vaccinated mice were non-protective. It is possible that regulatory Trm cells, which are typically not associated with host resistance to fungal infection, dampen the protective effects of Th17 cells (de Araujo et al, 2017;Galdino et al, 2018). It has been shown, that zymosan (predominantly composed of β1,3 glucan) can induce anti-inflammatory effects on T cell differentiation and promote the generation of regulatory T cells (Caminschi et al, 2019;Dillon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…10, 38,39 Th17 and Treg cells always play opposing roles in fungal infection. 12,27,40 An impaired balance of Th17/Treg is associated with disease progression, while the inhibition or depletion of Treg cells could potentially rescue Th1/Th17 immunity and improve prognosis. 12,27,40 Foxp3 could inhibit RORγt and down-regulate the expression of RORγt-mediated IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…12,27,40 An impaired balance of Th17/Treg is associated with disease progression, while the inhibition or depletion of Treg cells could potentially rescue Th1/Th17 immunity and improve prognosis. 12,27,40 Foxp3 could inhibit RORγt and down-regulate the expression of RORγt-mediated IL-17. 41 Therefore, the dominance of Treg cells could be associated with the down-regulation of RORγt expression and the suppression of Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that Treg cells can be protective or deleterious to P. brasiliensis infected mice 34,35,67,68 . At all post-infection times assayed, a reduced presence of Treg cells was here observed in line with reduced Foxp3 mRNA detected and the low levels of IL-10, TGF-β and IL-35, cytokines involved in the suppressive activity of this T cell subpopulation.…”
Section: Scientific Reports |mentioning
confidence: 99%